Work from Home during Pandemic of Covid-19: Effects on Work Life Balance and Job Satisfaction - Irma Suryani; Megawati Megawati; Sari Rahmani (Universitas Syiah Kuala, 2021)
Objective– This study is intended to see the relationship among three variables namely work from home, work life balance, and job satisfaction particularly during COVID-19 pandemic.Design/methodology– The research is a descriptive research method. Using online ques-tionnaire, a total of 150 higher education lecturers in Universitas Syiah Kuala, Aceh, Indonesia participated in the survey. The survey was conducted in December 2020. The data was ana-lyzed using SPSS.Results – This research revealed that there is a significant relationship between work from home and job satisfaction during COVID-19 outbreak in higher education lecturers, with the intervening variable of Work-Life balance also shows a significant impact toward job satisfac-tion.Research limitations/implications – This study has some limitation namely the small amount of data sample and focus only in one sector of sample participants (higher edu-cation lecturers), also this study only exercise three variables, meanwhile it is important to seek both personal and social factors such as person personality, behavior tendency, etc.Novelty/Originality – This study covers the impact of COVID-19 pandemic towards job related issues in the university context with participants mainly the lectures.